Pengabdian Kepada Masyarakat Tumbuh Kembang Balita Melalui Program Kegiatan Posyandu Desa Sambungrejo Kecamatan Sukodono Kabupaten Sidoarjo - Eva Khusnia Arianti; Mujia Yahdillah; Nailul Ulah Al Chumairoh Machfud; Fayola Issalillah; Adi Herisasono; Didit Darmawan; Suwito Suwito (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2023)
Active growth and development monitoring for early detection growth gaps (malnutrition or poor nutritional status, short children), developmental growth gaps (speech delays) and mental and emotional distortions of children (concentration disorders and hyperactivity). The purpose of this community service is to increase public knowledge about normal toddler growth and development, educate mothers about the importance of stimulating toddler growth and development. A survey conducted by the Community Service team, especially mothers with young children, said the lack of education was caused by the posyandu, especially in terms of toddler growth and development. How to spread this service with discussions, questions and answers, and checking the weight of toddlers. The service is carried out at the Connectrejo Village Hall with secondary targets for mothers who have toddlers. After the counseling activities, participants understand how to monitor the growth and development of toddlers and can monitor the ideal weight of toddlers.